2009
DOI: 10.1016/j.virol.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Sialic acid recognition is a key determinant of influenza A virus tropism in murine trachea epithelial cell cultures

Abstract: Influenza A virus interacts with specific types of sialic acid during attachment and entry into susceptible cells. The precise amino acids in the hemagglutinin protein that control sialic acid binding specificity and affinity vary among antigenic subtypes. For H3 subtypes, amino acids 226 and 228 are critical for differentiating between α2,3- and α2,6-linked forms of sialic acid (SA). We demonstrate that position 190 of the HA from A/Udorn/307/72 (H3N2) plays an important role in the recognition of α2,3-SA, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
(100 reference statements)
0
36
0
Order By: Relevance
“…In human H3 viruses, amino acid positions D190, L/I226, and S228 correlated with SA␣-2,6 receptors, while in swine H3 viruses those positions are D/A190, V226, and S228 (27,40,46). All three isolates-A/IN A(H3N2)v, Sw/PA H3N2-TRIG, and Sw/IL rH3N2p-were able to infect and transmit to contact pigs.…”
Section: Discussionmentioning
confidence: 94%
“…In human H3 viruses, amino acid positions D190, L/I226, and S228 correlated with SA␣-2,6 receptors, while in swine H3 viruses those positions are D/A190, V226, and S228 (27,40,46). All three isolates-A/IN A(H3N2)v, Sw/PA H3N2-TRIG, and Sw/IL rH3N2p-were able to infect and transmit to contact pigs.…”
Section: Discussionmentioning
confidence: 94%
“…It should be noted that the absence of pulmonary PR8 infection after URT delivery of virus was not due to a higher susceptibility of the virus to innate inhibitors in the LRT, since PR8 virus grew to high titers in the lungs after TRT infection. In addition, the inability of PR8 virus to progress to the lungs is independent of receptor specificity, as both viral strains have the capacity to infect cells bearing sialic acid in ␣2-3 linkage (20)(21)(22) to galactose, which is found on the receptors for influenza virus throughout the mouse respiratory tract and is used when these viruses grow in the lungs after TRT delivery (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that IAV preferentially replicate in tracheal epithelial cells (8,26). We analyzed the sites of initial viral replication and the spreading from these sites in the murine model by performing whole-organ imaging of NS1-GFP-infected lungs.…”
Section: Discussionmentioning
confidence: 99%